2016
DOI: 10.1093/ofid/ofw205
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Herpes Zoster in Individuals on Biologics, Disease-Modifying Antirheumatic Drugs, and/or Corticosteroids for Autoimmune Diseases: A Systematic Review and Meta-Analysis

Abstract: Background.Studies examining the risk of herpes zoster (HZ) associated with immunosuppressants, such as biologics, nonbiological disease-modifying antirheumatic drugs (nbDMARDs), or corticosteroids, have generated conflicting results.Methods.We conducted a systematic literature search from January 1946 to February 2016. Search terms related to HZ, rheumatoid arthritis, psoriasis, psoriatic arthritis, systemic lupus erythematous, or inflammatory bowel disease, biologics, nbDMARDS, and corticosteroids were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 93 publications
2
65
0
7
Order By: Relevance
“…Other studies have found that MTX was associated with HR of 3.02 for HZ in RA patients and HR of 3 in SpA patients . The use of DMARDs in general was associated with increased risk of HZ, as shown in a meta‐analysis by Marra et al, and with adjusted odds ratio of 1.27 and 1.37 in RA patients from two retrospective studies . Nonetheless, a recent population‐based cohort in Taiwan failed to show the increased risk of HZ in patients with SpA .…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have found that MTX was associated with HR of 3.02 for HZ in RA patients and HR of 3 in SpA patients . The use of DMARDs in general was associated with increased risk of HZ, as shown in a meta‐analysis by Marra et al, and with adjusted odds ratio of 1.27 and 1.37 in RA patients from two retrospective studies . Nonetheless, a recent population‐based cohort in Taiwan failed to show the increased risk of HZ in patients with SpA .…”
Section: Discussionmentioning
confidence: 91%
“…These findings should be considered alongside reports of an increased risk of HZ infection in patients with inflammatory disease, including psoriasis, treated with some biologics. [43][44][45][46][47] Although there has been some controversy around the level of HZ risk associated with biologics for inflammatory disease, 44,[48][49][50] there appears to be strong evidence suggesting an increased risk with monoclonal tumor necrosis factor-a inhibitors, 46,47 and particularly with infliximab. 43 However, an analysis of US health plan data suggested that the HZ risk associated with tofacitinib in rheumatoid arthritis patients was approximately double that with biologics.…”
Section: Discussionmentioning
confidence: 99%
“…B. im höheren Alter oder unter immunsuppressiver Therapie) hervorgerufen. Das Risiko für das Auftreten eines Herpes zoster ist bei Immunsupprimierten deutlich erhöht [50,[68][69][70][71]. Diese Personen sollten daher gegen Herpes zoster geimpft werden.…”
Section: Herpes Zosterunclassified